Mycobacterium tuberculosis protein MoxR1 enhances virulence by inhibiting host cell death pathways and disrupting cellular bioenergetics - Quadir, Neha; Shariq, Mohd; Sheikh, Javaid Ahmad; Singh, Jasdeep; Sharma, Neha; Hasnain, Seyed Ehtesham; Ehtesham, Nasreen Zafar (Virulence, 2023)
Mycobacterium tuberculosis (M. tb) utilizes the multifunctionality of its protein factors to deceive the host. The unabated global incidence and prevalence of tuberculosis (TB) and the emergence of multidrug-resistant strains warrant the discovery of novel drug targets that can be exploited to manage TB. This study reports the role of M. tb AAA+ family protein MoxR1 in regulating host-pathogen interaction and immune system functions. We report that MoxR1 binds to TLR4 in macrophage cells and further reveal how this signal the release of proinflammatory cytokines. We show that MoxR1 activates the PI3K-AKT-MTOR signalling cascade by inhibiting the autophagy-regulating kinase ULK1 by potentiating its phosphorylation at serine 757, leading to its suppression. Using autophagy-activating and repressing agents such as rapamycin and bafilomycin A1 suggested that MoxR1 inhibits autophagy flux by inhibiting autophagy initiation. MoxR1 also inhibits apoptosis by suppressing the expression of MAPK JNK1/2 and cFOS, which play critical roles in apoptosis induction. Intriguingly, MoxR1 also induced robust disruption of cellular bioenergetics by metabolic reprogramming to rewire the citric acid cycle intermediates, as evidenced by the lower levels of citric acid and electron transport chain enzymes (ETC) to dampen host defence. These results point to a multifunctional role of M. tb MoxR1 in dampening host defences by inhibiting autophagy, apoptosis, and inducing metabolic reprogramming. These mechanistic insights can be utilized to devise strategies to combat TB and better understand survival tactics by intracellular pathogens.